Curiosity and time: from not knowing to almost knowing. Issue 3 (3rd April 2017) - Noordewier, Marret K.; van Dijk, Eric
ABSTRACT: How does it feel to be curious? We reasoned that there are two sides to curiosity: not knowing something (i.e. information-gap) and almost knowing something (i.e. anticipation of resolution). In three experiments, we showed that time affects the relative impact of these two components: When people did not expect to close their information-gap soon (long time-to-resolution) not knowing affected the subjective experience of curiosity more strongly than when they expected to close their information-gap quickly (short time-to-resolution). As such, people experienced less positive affect, more discomfort, and more annoyance with lack of information in a long than a short time-to-resolution situation. Moreover, when time in the long time-to-resolution setting passed, the anticipation of the resolution became stronger, positive affect increased, and discomfort and annoyance with lack of information decreased. Time is thus a key factor in the experience of curiosity.